Raw Silk Quality Index Comparison between Electronic Tester and Seriplane Test System (Journal of Fiber Bioengineering and Informatics, 2014)
A new electronic tester consisting of capacitive sensors and optical sensors is now introduced into raw silkinspection. Compared with the traditional seriplane test, the quality indices change a lot. In assessingthe yarn evenness, the electronic tester measures the coefficient of variation of the raw silk size (CV_{even}%,CV_{5 m}%, CV_{50 m}%), while the seriplane uses evenness II. In assessing the yarn defects, the electronictester measures the slubs, thick places and thin places, SIE (small imperfection element), while theseriplane test uses cleanness and neatness. However, raw silk users who have been used to the seriplanetest report want to know how to interpret the electronic test indices, they want to be convinced byknowing the correlation between the indices of the two test systems. In this study 50 lots of raw silk aresampled and tested by the two test systems, and the correlation coefficients of the corresponding indicesare computed and analyzed. The result shows that there are significant correlation between evenness IIand CV_{5 m}%, a strong correlation between cleanness and slub by the optical sensor, a strong correlationbetween neatness and SIE by both the capacitive and the optical sensor, and a strong correlation betweenneatness and the thick and thin places by optical sensor. The result confirms the substitution of theelectronic test for seriplane test in future from the technical viewpoint.